2015
DOI: 10.1098/rspb.2015.1198
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to static electric fields leads to changes in biogenic amine levels in the brains ofDrosophila

Abstract: Natural and anthropogenic static electric fields are commonly found in the environment and can have both beneficial and harmful effects on many animals. Here, we asked how the fruitfly responds to these fields and what the consequences of exposure are on the levels of biogenic amines in the brain. When given a choice in a Y-tube bioassay Drosophila avoided electric fields, and the greater the field strength the more likely Drosophila were to avoid it. By comparing wild-type flies, flies with wings surgically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…It was shown, i.e., that octopamine may participate in the increase in cockroach behavioral activity induced by EMF exposure 40 . Also, another study showed that the static electric eld exposure elevated biogenic amine levels, including octopamine in the Drosophila brain 45 . The increase in motor activity after EMF exposure observed in the present study can also be associated with the octopamine level increase.…”
Section: Discussionmentioning
confidence: 98%
“…It was shown, i.e., that octopamine may participate in the increase in cockroach behavioral activity induced by EMF exposure 40 . Also, another study showed that the static electric eld exposure elevated biogenic amine levels, including octopamine in the Drosophila brain 45 . The increase in motor activity after EMF exposure observed in the present study can also be associated with the octopamine level increase.…”
Section: Discussionmentioning
confidence: 98%
“…aegypti use visual cues to locate their host [37]. It is therefore possible that they are more aware of the electric grid [38] or are unable to pick up as many short-range cues such as thermal and water-vapour cues [39,40].…”
Section: Traps and Hlc Measure Similar Protective Effect Of Trans Uthmentioning
confidence: 99%
“…After centrifugation of the homogenate at 17 000 g for 30 min at 4°C, the supernatant was collected. DA was measured using a C18 reverse phase column in a Hitachi 655A HPLC autosampler with a Coulochem M 5100A electrochemical detector (Newland et al, 2015). To control for dietary DA, we tried to detect DA in fly diet but the levels were below detection thresholds.…”
Section: Da Content Quantitationmentioning
confidence: 99%